The Association between Suicidal Ideation and Albuminuria in Korean Adults - Soo Jung Choi; Taehyun Nam; In Cheol Hwang (Tehran University of Medical Sciences, 2022)
Background: Data on the association between suicide and kidney function in the general population are scarce. This study evaluated albuminuria across suicidal ideation in Korean adults. Methods: We performed a cross-sectional study using data from the 2011 to 2013 Korean National Health and Nutrition Examination Survey. Overall, 14,101 adults were included in an examination of the amount of albuminuria associated with suicidal ideation. Suicidal ideation was measured using a self-reported questionnaire and albuminuria was assessed using the urinary albumin-to-creatinine ratio (ACR). Results: Various factors, including suicidal ideation, were associated with ACR. Multivariate regression analyses were stratified by age group and type 2 diabetes due to their strong relation to ACR. In the non-diabetic young group, individuals with suicidal ideation presented ACR 11.4 mg/g higher than those without suicidal ideation (P=0.038). Conclusion: In healthy young people, suicidal ideation is associated with increased albuminuria.